A functionalized polyamide acid additive for perovskite solar cells with high efficiency and stability. Issue 16 (6th April 2023) - Luo, Huanting; Tu, Fanlin; Chen, Xiaotong; Xing, Longjiang; Cao, Leliang; Ren, Guoxing; Ji, Shaomin; Zhong, Yuanhong; Xiao, Liangang; Chen, Wen-Cheng; Yang, Qing-Dan; Yang, Chen; et al.
Abstract : PAA as an additive enhances perovskite film crystallinity, enlarges grain boundaries, passivates defects, and improves efficiencies and stability of PSCs. Abstract : Perovskite solar cells (PSCs) have reached a certified power conversion efficiency (PCE) of 25.7% in 2022 benefiting from their high absorption coefficient, high carrier mobility, long diffusion length and tunable bandgap. However, due to the features of solution processing and rapid crystal growth of perovskite thin films, a variety of defects inevitably can form because of the precursor compositions and processing conditions. Actually, defects accumulating at the surface and grain boundaries are detrimental to both the device performance and stability of perovskite solar cells. Small molecules and polymers with functional groups have been employed to passivate the defects but suffer from complex synthesis processes and high costs. Herein, a novel polyamide acid (poly(6FDA- co -AHHFP); denoted as PAA) with multi-functional groups was developed by a one-pot method at room temperature and the polymer was introduced into a perovskite precursor solution as an additive to improve the perovskite film crystallinity, enlarge the grain boundaries, and passivate the defects, yielding enhanced PCE. PSCs with a 0.2 mg mL −1 optimized concentration of PAA exhibit a PCE of 20.03% with a high fill factor (FF) of 80.34%. In addition, the device with PAA as an additive demonstrated less hysteresis than that without an additive, as well as excellent reproducibility. Meanwhile, the device with the PAA additive also showed enhanced operational stability compared to the reference one. This work presents a novel polymer prepared by a one-pot method used as an additive in perovskite solar cells to achieve high performance and stability.